Analysis of Pavement Structures - Das, Animesh (CRC Press, 2023)
Analysis of Pavement Structures brings together current research and existing knowledge on the analysis and design of pavements and introduces load and thermal stress analyses of asphalt and concrete pavement structures in a simple and step-by-step manner. For the second edition of this book, a new chapter on numerical implementation (using FEM) of pavement analysis is added along with topics such as mechanical modeling of granular materials, applications of convolution theorems in visco-elasticity, visco-elastic Poisson's ratio, concepts of fracture mechanics in relation to fatigue of asphalt mix, solution of semi-infinite and so forth.